Role of Digital Tools in Housing Design by Mass Customization - Dinçer, Ahmet Emre; Tong, Hakan; Çağdaş, Gülen (ICONARCH International Congress of Architecture and Planning, 2012)
The concept of housing has different meanings and values for each user. Until recently, this idea was ignored by design implementations done by logic of mass standardization to fulfill increasing needs of housing in mega cities. However, it has gained its popularity with new changing design approaches. This paper focuses on the potentials of digital design processes with support of generative tools and users' choices as an altemative to recent approaches ofhousing design. Accordingly, a new computational model based on the cellular automata and mass customization approaches is presented and its implementation, limitations and possibilities are discussed.